Chapter L'educazione civica e la Resistenza: prospettive di Public History of Education - Martinelli, Chiara (Public History of Education. Teorie, esperienze, strumenti, 2022)
The introduction of civic education in the scholastic curriculum has offered to schools new opportunities for coping with the study of Resistance movement and other events occurred in contemporary history. Through some relevant didactic unit, the paper aims at giving to teachers some pratical examples, using the methodology of the Public History of Education.